The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1534/genetics.116.189787
|View full text |Cite
|
Sign up to set email alerts
|

A Common Suite of Coagulation Proteins Function inDrosophilaMuscle Attachment

Abstract: The organization and stability of higher order structures that form in the extracellular matrix (ECM) to mediate the attachment of muscles are poorly understood. We have made the surprising discovery that a subset of clotting factor proteins are also essential for muscle attachment in the model organism Drosophila melanogaster One such coagulation protein, Fondue (Fon), was identified as a novel muscle mutant in a pupal lethal genetic screen. Fon accumulates at muscle attachment sites and removal of this prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…2G; details and references in Table S2). For instance, the FB-secreted fon has been previously detected in muscles and Droujinine et al 7 shown to regulate their functions (14). Moreover, we identified additional secreted proteins previously unknown to be produced by FB or to traffic to legs or muscles ( Fig.…”
mentioning
confidence: 60%
“…2G; details and references in Table S2). For instance, the FB-secreted fon has been previously detected in muscles and Droujinine et al 7 shown to regulate their functions (14). Moreover, we identified additional secreted proteins previously unknown to be produced by FB or to traffic to legs or muscles ( Fig.…”
mentioning
confidence: 60%
“…These experiments establish muscle as a key immuneresponsive tissue in the defense against infection in both invertebrates and vertebrates. Further supporting a shared connection between muscle maintenance and innate immunity, we recently identified fondue (fon) as essential for maintaining the extracellular matrix (ECM) of the larval muscle attachment site (MAS) (Green et al, 2016). The common suite of secreted hemolymph proteins that accumulate and function at the MAS were also found to act with Fon in its previously described role in coagulation (Bajzek et al, 2012;Lindgren et al, 2008;Scherfer et al, 2006).…”
Section: Introductionmentioning
confidence: 87%
“…Our results thus far show that knockdown of two genes required for muscle attachment (Tig and stck) activate local JAK-STAT signaling in muscle. We previously identified Fon as a novel ECM organizer in preserving larval MASs (Green et al, 2016). Owing to its strong detachment phenotype and the ability to bypass the embryonic lethality that complicates the analysis of similar mutants (i.e.…”
Section: Jak-stat Signaling Is Activated Locally In Response To Musclmentioning
confidence: 99%
See 2 more Smart Citations